Status Anak dalam Perkawinan Campuran: Kewajiban Negara dan Implikasi Hukum Perlindungan Hak Anak - Naswar, Naswar; Maskun; Abdul Rahman; Muhammad Mutawalli Mukhlis; Tia Ludiana (Faculty of Law, Universitas Pasundan, 2024)
A mixed marriage is a marriage between two people from different countries or cultures. This can give rise to various legal issues, especially related to the status of children born from the marriage. Mixed marriages have become increasingly common in this era of globalization. However, when couples with different nationalities This article examines various legal issues that often arise from mixed marriages, especially related to the status of children born from the marriage, both related to family law, civil law, and children's rights. This article aims to contribute to understanding the legal complexities that arise from mixed marriages such as the legal aspects of mixed marriages, the rights and obligations of mixed marriage couples, the implementation of the legal aspects of mixed marriages in Indonesia, and the challenges and solutions in the implementation of the legal aspects of mixed marriages and provide insights that can be used to formulate improvements in legal policies and protection of children's rights at the national and international levels. In compiling the article, the researcher chose to use a normative legal approach method, by searching for regulations and literature related to issues regarding the status of children in mixed marriages. The results or findings of this article are that there are rights and obligations of mixed marriage couples, for example, they have the right to obtain citizenship from their husband/wife and must ensure that their marriage complies with the provisions of Indonesian marriage law. The implementation of the legal aspects of mixed marriages in Indonesia...